Future Challenges - Jahn, Johannes; Miettinen, K.; Ogryczak, W.; Deb, K.; Shimoyama, K.; Vetschera, R. (Multiobjective Optimization - Interactive and Evolutionary Approaches, 2008)
Many important topics in multiobjective optimization and decision making have been studied in this book so far. In this chapter, we wish to discuss some new trends and challenges which the field is facing. For brevity, we here concentrate on three main issues: new problem areas in which multiobjective optimization can be of use, new procedures and algorithms to make efficient and useful applications of multiobjective optimization tools and, finally, new interesting and practically usable optimality concepts. Some research has already been started and some such topics are also mentioned here to encourage further research. Some other topics are just ideas and deserve further attention in the near future. © 2008 Springer Berlin Heidelberg.
UnivIS-Import:2015-04-20:Pub.2008.nat.dma.pama21.future